Muay Thai Martial Arts Development Planning - Savero, Imam Eliyan; Adnan, Aryadie; Argantos, Argantos; Purnomo, Eko (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Studi Purpose Muay Thai martial arts is one of the martial arts that originated from the land of Thai elephants. Muay martial arts entered in Indragiri Regency in 2019 and has been included in the guidance of the Indonesian National Sports Committee (KONI). In this study, the problems encountered by the researcher were regarding facilities and infrastructure, organizational attention, sports programs, athlete interests, and athlete recruitment. This study aims to see the development of muay thai martial arts in Indragiri Hulu Regency. Method This research is a qualitative descriptive research. This research method uses observation, interviews, and documentation. In this study, the author found that the facilities and infrastructure in muay thai martial arts in Indragiri Hulu Regency are still not optimal because there is no permanent gym for training. Result and Discussion The researcher also conveyed suggestions for this study so that the recruitment of athletes is carried out by entering the school extracurricular so that this muay thai martial arts develops rapidly among the community. Conclusion of the results of this study shows that muay thai martial arts in Indragiri Hulu Regency is still relatively new, it can be seen from the camp gym that is not permanent, then for the discipline of athletes during training needs to be considered again, and also the recruitment of athletes can be done by including this branch of martial arts in the school extracurricular so that the development of muay Thai martial arts develops rapidly.